Pemanfaatan Limbah Gypsum Sebagai Subtitusi Filler Dalam Campuran Aspal Panas Dengan Metode Perendaman Berulang - Salam, Muhammad Ilham; Nurdin, Abd. Rahim; Mallawangeng, Tamrin (Program Studi Teknik Sipil Universitas Bosowa, 2023)
This research was made using gypsum waste which is expected to improve the quality of asphalt concrete to the characteristics and meet the technical requirements to be used as road pavement materials. This study aims to analyze the characteristics of hot mix asphalt (AC-WC) using oil asphalt with variations of gypsum waste in repeated immersion. This study uses an experimental method, namely an experiment to get results, thus it will be seen the utilization of gypsum waste in asphalt concrete construction with variations in gypsum waste levels of 10%, 15%, and 20%. The results showed that the use of gypsum waste will affect the characteristics of the asphalt mixture